Rehabilitation in Parkinson Disease - Anna Maria Dobosiewicz; Piotr Chyba; Grzegorz Duda; Małgorzata Jankiewicz; Karolina Puszcz; Teresa Zmaczyńska (Kazimierz Wielki University, 2017)
Parkinson Disease is a neurodegenerative disease which pathogenesis is not well known. Gait and balance disorders are the most basic symptoms of PD. The occurrence of the symptoms depends on  phase of disease and patient's individual attributes. Rehabilitation is one of the possible way  to assuage the occurrence of the symptoms. Methods of  physiotherapy have to be chosen individually to every patient.  Using the methods correctly can help the patient to overcome the symptoms at daily life and improve their quality of life.